Methods of expressing religious beliefs through sacred numbers in the architecture and sport of Zurkhaneh - Deimary, Nima; Mohammadi, Mohammad (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Ancient sports, dating to the size of the history of Mithraism, have undergone many changes throughout history and have been mixed with Sufism and Shiism. As a result of these developments, Zurkhaneh’s building also has a distinct root in the Islamic era by preserving patterns of the ancient world. The structure and its components are based on beliefs and sentiments that have been exhibited in different shapes in the architecture of Zurkhaneh building throughout history, holding symbolic concepts like sacred numbers. As in other examples of Iranian architecture, it has played a major role in the formation of architecture and sports of Zurkhaneh. Examples like the octagonal Field of Zurkhaneh, which is a symbol of the eight gates of Paradise and commemorating the eighth Shiite Imam, and the dome is a symbol of unity. This research tries to investigate the effect of sacred numbers on formation of archery sports and Zurkhaneh architecture by using a descriptive and analytic approach and using library documents and resources.